The Effectiveness of Using Dyadic Essay Technique in Enhancing Writing Proficiency among First-Year Students at Islamic Senior High School 2 Karanganyar - Wahid, Hassenda Asidqu; Sujito, Sujito (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The dyadic essay involves students working in pairs to create essay prompts and corresponding model answers, exchanging these prompts, and then comparing their responses to the model solutions. This study aims to explore the significant difference in students' writing proficiency achieved through the implementation of the dyadic essay technique among first-grade students at Islamic Senior High School 2 Karanganyar. This investigation utilized an Experimental research design and was conducted at Islamic Senior High School 2 Karanganyar, where data was gathered from first-grade students in SCIENCE 1 and SCIENCE 2. First-grade of SCIENCE 1 served as the experimental group while first-grade of SCIENCE 2 served as the control group, totaling 59 students. Data collection involved administering tests, and analysis was conducted using the T-test formula. The results of the study indicate that students instructed through the Dyadic Essay Technique demonstrated significantly higher writing skills compared to those taught through Classroom Discussion. The mean writing score of students taught with the Dyadic Essay (75.24) exceeded that of students taught through Classroom Discussion (67.50), suggesting enhanced descriptive writing skills among the former. In conclusion, the Dyadic Essay Technique proves to be effective in teaching writing, facilitating a smoother teaching and learning process, enhancing students' descriptive writing abilities, fostering creativity in essay composition, and enabling students to better express their thoughts and emotions in writing.